A comparison of coronary angiography and myocardial perfusion studies, using quantitative scoring systems - Premsagar, Preesha; Aldous, Colleen; Esterhuizen, Tonya (SA Heart Journal, 2021)
Background: Results of myocardial perfusion for screening coronary artery disease (CAD), and angiography for diagnosing CAD, can be quantified using summed difference score (SDS) and Synergy between Percutaneous Coronary Intervention with Taxus and Cardiac Surgery (SYNTAX) score, respectively. Aim: The aim is to quantitatively compare myocardial perfusion studies with angiography amongst South African patients using scoring systems. Methods: SDS on myocardial perfusion and SYNTAX score on angiography were compared. Regional scores within each vessel (left anterior descending (LAD), circumflex and right coronary artery (RCA)) were also compared. Scores were further risk categorised and evaluated. Results: The weak correlation between SDS and SYNTAX score (rs=0.210, p=0.015), became slightly negative when SYNTAX scores were stratified into low and intermediate-high risk groups. Regionally, LAD had very slight positive correlation (rs=0.171, p=0.048), circumflex (rs=0.164, p=0.058), and RCA (rs=0.116, p=0.184) no correlation. Conversely, comparison of scores categories was signifi cant (p=0.001). Conclusions: Inherent differences in the design of 2 scoring systems that evaluate the LAD territory may explain these findings. These differences were dominance, regional blood flow distribution and significant luminal diameter reduction. This study highlights the need to interpret myocardial perfusion results contextually during CAD screening.